Social cognition in schizophrenia. Issue 1 (22nd March 2017) - Charernboon, Thammanard; Patumanond, Jayanton
Abstract : Impairments in social cognitions in schizophrenia are increasingly reported in the last decade but only a few studies have come from Asia. The objective of the study was to evaluated emotion perception, theory of mind and social knowledge in people with schizophrenia compared to healthy controls. Participants were 36 clinically stable outpatients with schizophrenia and 36 normal controls with comparable age and level of education. We administered general neurocognition test (the Addenbrooke's Cognitive Examination), emotion perception (the Faces Test), theory of mind (the Eyes Test) and social knowledge (the Situational Features Recognition Test; SFRT). Schizophrenia patients displayed obvious impairment in all three social cognition domains i.e. the Faces Test [13.7 (2.9) vs 15.7 (1.9), P=0.001], the Eyes Test [18.9 (4.4) vs 23.5 (4.4), P<0.001] and SFRT [0.85 (0.09) vs 0.9 (0.05), P=0.002]. The performances on three social cognition tests did not correlate with positive symptoms. Only the Faces Test seemed to be related to negative symptoms. The results demonstrated that there are deficits of social cognitions in schizophrenia even in a clinically stable population.